2021
DOI: 10.31616/asj.2020.0323
|View full text |Cite
|
Sign up to set email alerts
|

Transtubular Anterior Cervical Foraminotomy for the Treatment of Compressive Cervical Radiculopathy: Surgical Results and Complications in a Consecutive Series of Cases

Abstract: Study Design: This was a retrospective review of patients with compressive cervical radiculopathy treated with a minimally invasive anterior cervical foraminotomy (ACF).Purpose: This study aimed to evaluate the results and complication rates of ACF in a consecutive series of patients and to report our clinical results of ACF as a minimally invasive technique in a series of 45 consecutive patients treated for compressive cervical radiculopathy.Overview of Literature: ACF is a motion-sparing procedure and an alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Surgery is applicable to patients with intractable or persistent pain despite sufficient conservative management for at least 6 to 12 weeks or to patients with severe or progressive neurological deficits. Cervical radiculopathy is treated surgically by anterior or posterior approaches [54]. For patients with cervical kyphosis [55], anterior procedures CTS, carpal tunnel syndrome; NCS, nerve conduction study; PIN, posterior interosseus nerve.…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…Surgery is applicable to patients with intractable or persistent pain despite sufficient conservative management for at least 6 to 12 weeks or to patients with severe or progressive neurological deficits. Cervical radiculopathy is treated surgically by anterior or posterior approaches [54]. For patients with cervical kyphosis [55], anterior procedures CTS, carpal tunnel syndrome; NCS, nerve conduction study; PIN, posterior interosseus nerve.…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…A risk of this procedure is that it is relatively unfamiliar; the aggregate published case series in the literature sum to less than 500 total cases. 2 This unfamiliarity combined with the required bone removal near the vertebral artery intuitively carries a higher risk of vertebral artery injury than alternative procedures, which has likely limited the adoption of this technique. Additionally, the greater lateral retraction or the resection of a small portion of the longus colli carries a risk of a postoperative Horner's syndrome.…”
Section: Transcriptmentioning
confidence: 99%
“…Additionally, the greater lateral retraction or the resection of a small portion of the longus colli carries a risk of a postoperative Horner's syndrome. 1,2 Last, given the disc-sparing nature of this technique, recurrent disc herniation is possible. 3 The alternative procedures were not chosen for the same reasons discussed on the previous slide-we prioritized preserving the cervical disc and motion segment, avoiding hardware implantation, and minimizing tissue disruption, postoperative pain, and postoperative restrictions.…”
Section: Transcriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Posterior cervical foraminotomy (PCF) is an effective surgical method for the treatment of cervical radiculopathy which revision rate and clinical efficacy are reported to be similar with that of anterior cervical discectomy and fusion (ACDF). [1][2][3][4] It also can avoid troublesome postoperative complications of ACDF including pseudarthrosis, adjacent segmental disease, loss of motion segments, and postoperative dysphagia. 5,6 Furthermore, recent reports have demonstrated that PCF results in shortened hospital stay and reduced blood loss or cost compared to ACDF which makes PCF a widely applied surgical option for cervical radiculopathy.…”
Section: Introductionmentioning
confidence: 99%